ANALYSIS OF THE BEHAVIOR OF CHARACTERS IN THE FILM 'WONDER' FOR STRENGTHENING ANTI-BULLYING EDUCATION IN FIFTH GRADE ELEMENTARY SCHOOL - Abbas, Nur Anisa; djaini, Nuriska; Putri Lasaka, Giska; Kaili, Nur Fatima; Ntuiyo, Putri Aisa; Tebai, Apin (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2025)
This research aims to analyze the characterization of Jack in the film Wonder (2017). Wonder is an American family drama film released in 2017, directed by Stephen Chbosky and produced by Michael Beugg, Clark, David Hoberman, and Todd Lieberman. It was written by Jack Thorne, Steve Conrad, and Stephen Chbosky based on the novel Wonder by R.J. Palacio. The film tells the story of a boy with physical disabilities named August Pullman who experiences bullying at school. Jack is one of the characters who wants to befriend August Pullman. The identified data is analyzed according to the intrinsic approach by Edgar V. Roberts as cited by Rondonuwu (13) in the analysis of the main character writing in the film Barbie of Swan Lake. This research shows that the character Jack has the traits of Caring, Loyal, Brave, and Kind in the film Wonder (2017).